The Effectiveness of Using the Shopee Application on the Success of Online Businesses of Social Science Education Department Students at IAIN Syekh Nurjati Cirebon (A Social Science and Entrepreneurship Journal, 2024)
This research is motivated by the increasingly sophisticated development of the era in the field of entrepreneurship, but along with the development of this technology, only a few of the Tadris IPS students have tried entrepreneurship through the Shopee application and succeeded until their business can grow. The Shopee application is an online marketplace platform that bridges buyers and sellers to facilitate the buying and selling transaction process. The type of research used in this study uses a qualitative approach with a descriptive method to understand phenomena holistically in the form of words and language. Data collection techniques use observation, interviews and documentation. Data analysis uses data collection, reduction, data presentation and conclusions. The results of this study include: 1) Use of the Shopee application on the online store of Tadris IPS students, The time needed to create a shop on the Shopee application until the shop can be used is around 10 minutes. 2) The level of success of the online store business of Tadris IPS students, the turnover they get from the online store on the Shopee application ranges from 5 to 8 million per month. 3)  effectiveness of using the Shopee application on the success of the online shop business of students of the Tadris IPS Department is very effective because the Shopee application provides a very complete payment system.
Keywords: Business Success; Shopee Application; Effectiveness